Avaliação das competências gerenciais descritas pelo GESTCOM para a UFPA com as competências de gestão extraídas do critério governança do modelo de excelência em gestão pública - ROCHA, Gualter de Oliveira (Universidade Federal do Pará, 2019)
This study aimed to evaluate the alignment of managerial skills described by GESTCOM for UFPA with management skills taken from the governance of MEGP criteria. It is a nature applied research, exploratory and descriptive, which used a collection of bibliographic data and documents procedures, using the content analysis technique to meet the proposed objectives. The study was conducted in two stages. At first, the points of the dimension of governance MEGP were selected, extracted their requirements, applied the model proposed by Carbone et al. (2009) for the training of professional skills and, finally, registered management practices related to each competency. In the second phase, comparisons were made between the extracted managerial skills of MEGP with those identified in mapping skills of IFES by GESTCOM. They were also collated the competencies identified by GESTCOM with the framework of governance and management of TCU. nine skills and management practices have been described based on MEGP, totaling twenty-five management practices that managers must perform to meet the requirements suggested by the model. The analyzes show that servers in management positions need to develop management and leadership skills to maximize their performance and the challenges exposed in the public service; and the main of them is to be able to lead people through purposes waking consciousness in search of cultural change. This research also confirmed that efforts in mapping the UFPA skills, culminating in the identification of managerial skills to the institution are strongly aligned with the Excellence Model of Public Management and the proposed governance and leadership practices in Referential Basic Governance the Federal Audit Court